Synthesis, Characterization, and Antimicrobial Studies of Some Metal (II) Complexes of Some Azo Dyes - Aladesusi, Ruth Cecilia; Eke, Uche Basil (Bumi Publikasi Nusantara, 2023)
Azo compounds possess the R-N=N-R’ functional group are used as dyes and from the literature survey, their biological activities are enhanced when coupled with other transition metal complexes of Co(II), Cu(II), Mn(II), Ni(II) and Zn(II) with a novel bis azo dye 2, 2 1 [benzene-1, 3-diyl di(E) diazene 2,1-diyl] bis (4-chloroaniline) derived from mphenylenediamine and p-chloroaniline were synthesized. Data were supported by characterizations using UV-Vis spectroscopy and these compounds have been done based on elemental analysis, electronic data, Fourier Transform Infra-Red (FT-IR), 1H Nuclear Magnetic Resonance (NMR), powder X-ray diffraction and thermal analysis, and magnetic data. From the analytical and thermal data, the stoichiometry of the complexes is 1:1 (metal: ligand). Based on physicochemical data octahedral, tetrahedral, and square planar geometries were assigned for the complexes. The ligand and metal complexes were screened for their antimicrobial activity. The azo of 2-aminopyridine with its cobalt (II) complex exhibited antimicrobial activity at higher and lower concentrations.